(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Background: Infertility is defined as a failure of achieve a pregnancy after one year and more of regular unprotected sexual intercourse. The exposure of reproductive system to heavy metals has also been associated with male infertility. A large number of metals are toxicants to the reproductive system and are suspected to be endocrine system disruptors. Patients and methods: This study performed at the high institute of infertility diagnosis and assisted reproductive technologies in Al-Nahrain University and the Poisoning consultation center / specialized surgeries hospital in the Medical city in period from November 2018 to April 2019. Number of 150 men were enrolled in this study divided into two groups, the patient and the normal control groups. The infertile group included 100 men aged 20-50 years who they have abnormal seminal fluid analysis parameters. The second group included 50 healthy fertile men who have at least two children without any previous history of systemic diseases as a control group. Heavy metals and testosterone concentrations were estimated for all the study groups. Aim of current study are evaluation of some heavy metals concentrations, in serum and whole blood of groups. Assessment of testosterone hormone in serum of infertile men and healthy controls and study the correlation between this hormone and trace elements which were estimated among cases. Results: The heavy metals Cu, Pb and Cd showed a highly significant increase (p<0.01) in the serum and blood of infertile men (159.77±8.49 µg/dl, 24.18±4.30µg/dl, 0.31±0.10 µg/dl) respectively when compared with their concentrations in healthy control men (125.14±10.12 µg/dl, 15.74±2.69 µg/dl, 0.16±0.03 µg/dl) respectively. The mean levels of Zn showed a highly significant decrease (p<0.01) in the serum of infertile men (70.82±9.48 µg/dl) compared to its mean level in the healthy control group (95.70±11.41 µg/dl). Serum testosterone hormone in infertile men (185.40±61.92 ng/ml) showed a highly significant decrease (p<0.01) as compared with those of healthy men (450.35±131.27 ng/ml). Serum copper level was negatively correlated with serum testosterone level among infertile men. Conclusions: this study concluded that some heavy metals were shown to be an indicators for men infertility. Serum copper level was negatively correlated with serum Testosterone level among infertile men .This result can hypothesize that excess copper acts as a hormonal disrupter. The remaining heavy metals did not show significant correlation with the selected hormones.